The Influence of the Problem Based Learning and Attitudess towards Learning Outcomes for Mathematics - Antonius Yohan; Mustaji; Suryaman (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
This research aims to (1) to know the differences between the learning outcomes of students who follow the LBC and conventional learning, (2) to tell the difference between students who have learning outcomes learning the attitude of higher and lower (3) to know the interactions between models of learning and learning attitude towards learning outcomes. This research uses a type of quantitative research. Implementation observations data model Data and results of Problem Based learning questionnaire attitudes of the students analyzed inquantitative descriptive by determining the score and the percentage obtained every aspect is observed. The results showed that: (1) there is a difference between the learning outcomes of students who follow Problem Based Learning and conventional learning. (2) there is a difference between students who have learning outcomes learning the attitude of higher and lower (3) there are interactions between the learning model and attitudes towards learning outcomes.